Blood father [videorecording (DVD)] - Luna, Diego, 1979-; Gibson, Mel; Moriarty, Erin, 1994-; Parks, Michael, 1940-2017; Macy, William H., 1950- (LG Premiere, 2016)
When his estranged teenage daughter is targeted by a drug cartel, ex-convict John Link must call upon connections from his criminal past to save his daughter's future.